Failure analysis of air preheater tubes in a circulating fluidized bed boiler. (June 2021) - Suwarno, Suwarno; Nugroho, Giri; Santoso, Andik; Witantyo,
Highlights: APH tubes in the power plant boiler failed after five years in services. The temperature of the tube surface below the acid dew point temperature. The tube steel composition contains high phosphorus trigger high corrosion rate. A Combination of high sulfur content in the coal and the chemical composition of the steel accelerate corrosion. Abstract: A tubular air preheater (APH) is located at the cold end in the back pass region of a circulating fluidized bed (CFB) boiler. After five years of operation, a significant number of tubes at the air inlet section of the tube were found to have a leak. Some samples were taken from the site for laboratory analysis. Optical microscopy, scanning electron microscopy-energy dispersive spectroscopy, and other standard laboratory tests were used to analyze the samples. A computational fluid dynamics (CFD) simulation was performed to simulate the temperature distribution in the APH using typical operating parameters of the circulating fluidized bed boiler. Chemical analysis of the tube shows high phosphorus content in the steel above that allowable by the standard. Analytical calculation of the acid dew point temperature indicates that sulfuric acid condenses at 143 °C. The CFD analysis showed that the tube surface temperature has a skin temperature of less than 143 °C. This low skin temperature combined with high sulfur content in the coal triggers high condensation of sulfuric acid, which led to severe corrosion and leaks. The high phosphorus content of the steel amplifies the corrosion rate under sulfuric acid deposition. The present work shows how a high phosphorous content in steel accelerates corrosion by sulfuric acid in power plant equipment.